Keefektifan Kalimat pada Berita Politik di Surat Kabar Tribun Lampung - Maria Widhi Majesta Adiwena (Asosiasi Riset Ilmu Pendidikan Indonesia, 2025)
This research focuses on analyzing the use of effective sentences in political reporting in the Tribun Lampung Newspaper. With a descriptive qualitative approach, this research aims to describe how the sentences in political news are structured and to what extent they meet the rules of effective sentences. Research data uses reading, listening and note-taking techniques in various political articles published in the Tribun Lampung Newspaper. The results of the analysis show that most of the political news studied has implemented the principles of effective sentences well. Elements such as structural similarity, parallelism, decisiveness, economy, accuracy, coherence and logic can generally be found in these news sentences. This shows the Tribun Lampung Newspaper's efforts to present information that is clear, concise and easy to understand for readers. However, this research also identified several discrepancies with the rules of effective sentences in several news stories. Some sentences were found to contain unnecessary or convoluted words, thereby reducing the effectiveness of conveying the message. Apart from that, there are also sentences that are ambiguous or give rise to multiple interpretations, which can confuse readers. These findings indicate that although in general the Tribun Lampung Newspaper has made efforts to use good and correct language in political reporting, there is still room for improvement. It is hoped that this research can contribute to improving the quality of political news writing, both in the Tribun Lampung Newspaper and other mass media.